ALTERNATIF STRATEGI PENGEMBANGAN PELABUHAN PERIKANAN NUSANTARA BRONDONG LAMONGAN JAWA TIMUR - Agus Suherman (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
A strategy is increasingly needed by Nusantara Fishing Port (NFP) Brondong due to the tendency of the increasing intensity of competition in the national Fishing Port (FP). This strategy is derived from business strategy for inter-sector regulation on NPF Brondong have the same direction of motion for the achievement of targets NFP Brondong. The purpose of this study is to formulate development strategies NFP Brondong The method used a case study descriptive survey. The results of this study show that NFP Brondong development strategy include 1) optimizing the utilization of the potential of SDI, (2) to provide facilities that meet international standards, (3) maintenance and improvement of operational facilities of FP, (4) institutional capacity building, and (5) supervision and law enforcement